2000
DOI: 10.1128/aem.66.9.4098-4104.2000
|View full text |Cite
|
Sign up to set email alerts
|

Toluene-Degrading Bacteria Are Chemotactic towards the Environmental Pollutants Benzene, Toluene, and Trichloroethylene

Abstract: The bioremediation of polluted groundwater and toxic waste sites requires that bacteria come into close physical contact with pollutants. This can be accomplished by chemotaxis. Five motile strains of bacteria that use five different pathways to degrade toluene were tested for their ability to detect and swim towards this pollutant. Three of the five strains (Pseudomonas putida F1, Ralstonia pickettii PKO1, and Burkholderia cepacia G4) were attracted to toluene. In each case, the response was dependent on indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
160
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(170 citation statements)
references
References 45 publications
8
160
0
2
Order By: Relevance
“…To test for tactic reactions, we performed a set of classical chemotaxis experiments (swarm plates 8 , plug-in-pond assays 53 , mini-plug slides 54 , commercial microscope slide chemotaxis chambers (m-slide chemotaxis, Ibidi GmbH 16 ) with different carbon sources as putative attractants (lactate, NATURE COMMUNICATIONS | DOI: 10.1038/ncomms6398 ARTICLE pyruvate, acetate). Swarming occurred in soft agar with all chemicals tested, but no positive responses were detected in any other assay performed.…”
Section: Methodsmentioning
confidence: 99%
“…To test for tactic reactions, we performed a set of classical chemotaxis experiments (swarm plates 8 , plug-in-pond assays 53 , mini-plug slides 54 , commercial microscope slide chemotaxis chambers (m-slide chemotaxis, Ibidi GmbH 16 ) with different carbon sources as putative attractants (lactate, NATURE COMMUNICATIONS | DOI: 10.1038/ncomms6398 ARTICLE pyruvate, acetate). Swarming occurred in soft agar with all chemicals tested, but no positive responses were detected in any other assay performed.…”
Section: Methodsmentioning
confidence: 99%
“…In heterogeneous systems, bacterial motility is often biased by chemotaxis that guides bacteria toward higher concentrations of nutrients (or away from toxic compounds) [Fenchel, 2002;Stocker et al, 2008]. Chemotaxis has been observed in soil where motile bacteria show chemotactic response to a variety of pollutants considered as potential nutrient sources [Parales et al, 2000;Olson et al, 2004;Kohlmeier et al, 2005;Ford and Harvey, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies with Pseudomonas putida identified metabolic pathways dedicated to gasoline components, like benzene, toluene and xylene. Also, they show a schematic diagram of the metabolic pathways constructed in P. putida for degradation of the BTX mixture (12,15). The TOL pathway in BTX mixture biodegradation does not utilize benzene as a substrate (12).…”
Section: Introductionmentioning
confidence: 99%